Cross-National University Collaboration for Social Learning Innovation of the Six University Initiative Japan–Indonesia (SUIJI) Program in Indonesia - Ohashi, Koichi; Tamma, Sukri; Ibrahim, Muhammad Akmal; Hasniati; Rampisela, Dorothea Agnes; Yusuf, Muhammad (LP2M IAIN Palopo, 2025)
This paper examines the implementation of the Six University Initiative Japan–Indonesia (SUIJI) in South Sulawesi Province as a cross-national university based model of social innovation. The SUIJI program highlights the importance of direct engagement between universities, local communities, and youth particularly students in sustainable development projects. Using the frameworks of Grassroots Social Innovation and the Capability Approach, this study analysis SUIJI’s contributions to enhancing participants’ capabilities, fostering collaborative networks, and generating impacts on local communities. The research employed a qualitative case study method, drawing on interviews, observations, and document analysis. The findings demonstrate that SUIJI strengthens students’ intercultural competence, adaptive leadership, and reflective agency, while simultaneously encouraging collaborative innovations across diverse social domains that advance sustainable community welfare. The benefits extend beyond economic improvements, encompassing the reinforcement of social cohesion, environmental awareness, and sustainable lifestyles. Nonetheless, several challenges persist, including the dominance of top-down approaches, limited scholarship opportunities, language and cultural barriers, and asymmetrical power relations. This study concludes that SUIJI represents a model of best practice in the internationalization of higher education, grounded in inclusivity, grassroots empowerment, and tangible contributions to sustainable development.